The Ethical Concept of Production and Distribution in Islamic Economics from the Perspective Of M. N. Siddiqi - Febintha Sistyamurti; Rokhmat Subagiyo; M. Aqim Adlan (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
Islamic economics attempts to regulate human economic activities based on Sharia principles sourced from the Qur'an and Al-hadith. In Islam, human activities are not only assessed as worldly but also spiritually assessed or must think about life in the hereafter, including economic activities. MN Siddiqi focuses his thoughts on economic activities, namely, production, distribution, and takaful. This study aims to determine the concept of production and distribution ethics in Islamic economics from the perspective of M.N. Siddiqi by using a qualitative approach and library research in the form of books, journal literature, and other research results relevant to this research. Based on the results of the study, production, and distribution are activities whose main purpose is to meet the needs of all mankind. In Islamic economics, there is the concept of Islamic economic ethics so that production and distribution activities do not deviate from the main objectives. According to Muhammad Nejatullah Siddiqi, if the ethics of production and distribution are carried out honestly and fairly, it will have a good impact on the Islamic economy in its efforts to meet the needs of all people.